Low-Dose Cyclophosphamide Induces Nerve Injury and Functional Overactivity in the Urinary Bladder of Rats - Wang, Rui; Hong, Ming; Huang, Jingyi; Zhou, Na; Zhang, Yao; Xu, Siyuan; Liu, Jiaye; Yuan, Junjie; Zhang, Lusiqi; Huang, Linyuan; Huang, Ping; Tan, Bo; et al. (Frontiers in Neuroscience, 2021)
Aim: This research aimed to investigate the neurotoxicity of low-dose cyclophosphamide (CYP) on the urinary bladder of rats by in vivo and in vitro studies. Methods: To establish CYP-induced cystitis rat model, rats were treated with three intraperitoneal injections of CYP (25 mg/kg) in a week. During treatment, the up‐down method was used to assess the mechanical withdrawal threshold. On day 8, urodynamic test and bladder smooth muscle contractility study, including the contraction of bladder strips to electrical field stimulation (EFS, 2–64 Hz), carbachol (CCh, 10−8–10−5 M) and KCl (120 mM), were performed to evaluate the function of bladder function. Body weight and bladder weight were also recorded. Morphometric analysis using an optical microscope and transmission electron microscope was performed to observe the changes of microstructure and submicrostructure of the bladder. The major pelvic neurons were isolated and treated with acrolein (the main CYP metabolite) to assess apoptosis in vitro. RT-PCR assays were used to quantify the mRNA expression levels of Nlrp6, Asc, Casp11 and Casp1 in bladder tissues and primary neurons. Results: After CYP injections, the body weights decreased, but the the bladder weights increased in the model group. The mechanical withdrawal threshold of the cystitis model remained at a low level. The morphometric analysis suggested bladder inflammation and neuroinflammation in the bladder of the cystitis rat model. Urodynamic test revealed that, the amplitude, the pressure baseline, the peak pressure and pressure threshold of model rats significantly increased after CYP treatment. The muscle strips of model rats exhibited significantly higher contractility caused by EFS and CCh than the controls. Apoptotic cells appeared at the highest concentration group (100 µM acrolein) after 6 h of acrolein incubation in apoptosis assay of primary neurons. The mRNA expression levels of Nlrp6 and Casp11 were significantly increased in the the cystitis rat model and in the acrolein-treated neurons. Conclusions: Low-dose CYP treatment was confirmed to induce nerve injury, which leading to bladder pain and overactive bladder in female rats, and the up-regulation of Nlrp6 and Casp11 may contribute to these pathological changes.